ANALYSIS OF HAND HYGIENE PRACTICES AMONG HEALTH CARE WORKERS FOR PREVENTION OF NOSOCOMIAL INFECTION: A SYSTEMATIC REVIEW - Juliana, Mutia; M.G Sianipar, Imelda; Aditya Willyanto, Nathan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Hand hygiene has been regarded as the most efficient technique in nosocomial infections control. Aim: This study aims to summarize and evaluate the impact of hand hygiene practices among health care workers for prevention of nosocomial infection. Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2019–2023. Duplicate publications, review articles, and incomplete articles were excluded. Results: The databases search identified a total of 19.427articles (Table 1). Of these, 120 articles passed the screening process, resulting in 20 articles for full-text assessment. Among them, 13 articles contain insufficient details regarding the focus of interest. Hence, we found 7 appropriate studies. Conclusion: Our study found that hand hygiene practices is a preventive measure for NIs and it seems that hand rubbing appeared to be more effective than hand washing as a hand-hygiene strategy, albeit with evidence of low to moderate quality. This strategy promotes the use of hand-rubbing in intensive care units for improved clinical outcomes for patients and healthcare providers.